Answer: y = 3x + 1
Explanation:
First of all, Slope Intercept form is this equation;
y = mx + b
y = the y-coordinate
m = slope of the line ( Remember that this type of equation is ALWAYS linear)
x = the x-coordinate
b = is the y-intercept
We can substitute the given values into the equation to find the y-intercept, b.
==> y = mx + b
==> -5 = 3(-2) + b (simplify)
==> -5 = -6 + b (add 6 to both sides to isolate the variable)
==> 1 = b
Since we have the b, the y-intercept , we can write the standard slope-intercept equation;
y = 3x + 1
Hope this helped! Have a good day ;)